Analisis Framing Pemberitaan Kasus Little Aresha pada CNN Indonesia, Kompas.com, dan Detiknews - Lailatul Ramah; Muhammad Anshori; Kristya Nur Asiyah (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2026)
The research problem of Analysis of Framing of News Reporting of Little Aresha Case on CNN Indonesia, Kompas.com, and Detiknews lies in the possibility of differences in the way the three media frame facts, choose sources, and highlight certain aspects of the same case so that they can form different public perceptions of the event. Therefore, this research is important to identify the construction of reality built by each media and understand how the framing process influences the delivery of information to the public. This study aims to analyze how online media framed the news coverage of alleged child abuse cases at Little Aresha Daycare Yogyakarta on CNN Indonesia, Kompas.com, and Detiknews. This research used a qualitative method with the framing analysis approach of Zhongdang Pan and Gerald M. Kosicki through syntactic, script, thematic, and rhetorical structures. The results showed that CNN Indonesia framed the case from a victim protection perspective, Kompas.com emphasized institutional responsibility and law enforcement, while Detiknews focused more on the chronology of events and the facts of the violence that occurred. These framing differences indicate that the media play an important role in shaping public opinion through language selection, fact emphasis, and specific perspectives in news reporting